Key lessons learned from the immunization supply chain of Malawi, an African country using EVM2.0. (December 2022) - Sethy, Ghanshyam; Nenani Chisema, Mike; Sharma, Lokesh; Folorunso, Olamide; Haile, Dereje; Reda Berri, Zeinab; Joshi, Krupal; Ntenje, Mphatso; Mitambo, Collins; Laher, Beverly; Singhal, Sanjay; Chirwa, Samuel; et al.
Abstract: Objectives: A country's immunization system's effectiveness depends on its supply chain's efficacy. To assess the challenges of maintaining an efficient vaccine supply chain, Malawi conducted its assessment using The EVM2.0 tool (Effective Vaccine Management). Methods: It is a cross-sectional study in which all EVM requirements were assessed between September and October 2021. Data were collected from eighty-two randomly selected sites using the site selection tool of the EVM. Data were entered into the EVM assessment tool 2.0 version 1.12 for analysis. This tool generates performance indicators and criteria scores for assessed sites, compared with a WHO minimum score of 80%. Results: Overall criteria scores across all levels of the immunization supply chain showed a statistically significant mean difference of 5.92 (t = 2.58, P = 0.02). Comparative overall mean criteria scores across different levels of the immunization supply chain showed no statistically significant difference for primary (p = 0.76), sub-national (p = 0.69), and lowest distribution stores (p = 0.12). However, a substantial gap was found in the overall mean scores of the health facility's service point (SP) (t = 4.12, P = 0.001). The overall category scores across all immunization supply chain levels did not show a statistically significant difference. However, among individual category scores, Infrastructure (76 %), Equipment (67 %), Policies and procedures (62 %), Financial (47 %), and Resources (64 %) were found to be below the WHO minimum score. Conclusion: Though the 2021 Malawi EVM assessment findings are promising, they still identified the gaps to be improved to ensure the vaccine availability in the right amount, at the right time, and at the right cost.